PENGARUH TEMAN SEBAYA TERHADAP KEPERCAYAAN DIRI SISWA KELAS X DI SMA NEGERI 10 PALEMBANG - Khairunnisa, Mutia Najwa; Pravitasari, Okti; Rahman, Annisa; Farenta, Argina; Septiani, Denisa; Widi Putantri, Novi Fayza; Utami Ramadhani, Oktavia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of peer support on the self-confidence of tenth-grade students at SMA Negeri 10 Palembang. This research is motivated by the importance of self-confidence in supporting students’ personal development and success in the learning process, as well as the fact that some students still have low levels of self-confidence. The method used is a quantitative approach with a non-experimental research design, involving all tenth-grade students as the population and sample through a saturated sampling technique. Data were collected using a Likert-scale questionnaire measuring peer support through emotional, appraisal, instrumental, and informational aspects, as well as self-confidence through self-belief, courage, and optimism. The data were analyzed using simple linear regression, coefficient of determination, and significance testing. The results show that peer support has a positive and significant effect on students’ self-confidence, as indicated by a significance value of 0.004 (< 0.05) and a regression coefficient of 0.367. The coefficient of determination value of 0.136 indicates that peer support contributes 13.6% to students’ self-confidence, while the remaining variance is influenced by other factors outside this study. Therefore, it can be concluded that peer support plays a role in improving students’ self-confidence, although its contribution is relatively low, and support from various parties is needed to optimize the development of students’ self-confidence.